2014
DOI: 10.12659/msm.890119
|View full text |Cite
|
Sign up to set email alerts
|

A new device to test cutting efficiency of mechanical endodontic instruments

Abstract: BackgroundThe purpose of the present study was to introduce a new device specifically designed to evaluate the cutting efficiency of mechanically driven endodontic instruments.Material/MethodsTwenty new Reciproc R25 (VDW, Munich, Germany) files were used to be investigated in the new device developed to test the cutting ability of endodontic instruments. The device consists of a main frame to which a mobile plastic support for the hand-piece is connected and a stainless-steel block containing a Plexiglas block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 36 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…This is in agreement with previous studies that showed that Reciproc instruments removed more dentin along the canal. [ 13 14 ] A sharp double cutting edge S-shaped geometry, smaller cross-sectional area,[ 15 ] and the dissimilarities between tapers of the master apical instruments may explain the greater cutting ability of Reciproc instruments. In the present study, the final taper was 0.08 at the apical 3 mm for Reciproc, 0.04 for S5 and TF.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies that showed that Reciproc instruments removed more dentin along the canal. [ 13 14 ] A sharp double cutting edge S-shaped geometry, smaller cross-sectional area,[ 15 ] and the dissimilarities between tapers of the master apical instruments may explain the greater cutting ability of Reciproc instruments. In the present study, the final taper was 0.08 at the apical 3 mm for Reciproc, 0.04 for S5 and TF.…”
Section: Discussionmentioning
confidence: 99%
“…A cyclic fatigue testing device, which had been validated in previous studies, was used [18,19]. The device consists of a mobile platform connected to an electric handpiece that allows a precise and repeatable placement of the tested instruments inside the artificial root canal and a stainless steel block containing the artificial canals (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have been conducted to analyze their properties, such as cutting efficiency during preparation 8 , preservation of the anatomical path of the root canal 9 , instrumentation time 10 , and production of dentin debris 11 . This study compared three factors (cutting capacity, preparation time, and occurrence of apical deviation) for preparation of canals with the WaveOne ® and Reciproc ® reciprocating systems.…”
Section: Discussionmentioning
confidence: 99%